(untitled) (Economics and region, 2024)
The strategic foundations of ensuring a security-oriented international space, including its economic, informational and ecological dimensions are investigated in the article. It was determined that one of the key aspects of ensuring a security-oriented international space is the development and implementation of national strategies for security-oriented development. It has been proven that the synthesis of economic, information and ecological security in the form of a single ecological-informational-economic security becomes an important condition for achieving sustainable development. The main indicators of measuring the security environment by the components of economic, information and ecological security are proposed. The main principles on which the approaches to the formation of ecological, informational and economic security are based are substantiated. The article focuses considerable attention on the mechanism of formation the modern dimensions of ecological, informational, and economic security at the global, national, and regional levels. The main dimensions of ecological, informational and economic security corresponding to the modern paradigm of security-oriented international space are considered.